Representation Of Nojoud's 'Early' Marriage: A CDA Of Online English-Language Yemeni Newspapers - Abduljalil al-Sharabi,; Noraini Ibrahim,; Nor Fariza Mohd Nor, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Online English-language newspapers in Yemen are considered official windows through which Yemen is portrayed to the global world. Investigating the representation of a Yemeni social event (the Nojoud’s phenomenon) to foreign readers, this paper specifically aims to identify the discourses that the newspaper texts draw upon in representing ‘early marriage’ in Yemen. Besides, it investigates the assumptions that the texts presuppose and the way the social actors are identified. As a qualitative analytic research, Fairclough’s critical discourse analysis as well as Kress and van Leeuwen’s (critical) multimodal discourse analysis employed the micro and macro discourse analysis of the online version of Yemen Times newspaper. Data analysis reveals that the selected texts draw upon a number of foregrounded and backgrounded discourses in representing ‘early marriage’ in Yemen including backgrounded Yemeni legal discourse,backgrounded Sharia discourse of ‘maturity’, and fore grounded discourse of minimum age of 18, and fore grounded discourse of sexual abuse. Simultaneously, it is uncovered that the texts presuppose many assumptions such as ‘marriage in Islam’, ‘puberty’ and the ‘age documentation’ in Yemen. While some of the important social actors are absent, the main social actors in the represented case are mainly identified by ‘overwordings’ of the age. This paper ends by offering several suggestions and recommendations that would benefit EFL (Yemeni) students, teachers, curriculum designers, journalists and translators when dealing with English-language texts reporting on local phenomenon.